2007
DOI: 10.1039/b714921b
|View full text |Cite
|
Sign up to set email alerts
|

Iodine assisted palladium catalyzed ring opening of bicyclic hydrazines with organoboronic acids: stereoselective synthesis of functionalized cyclopentenes and alkylidene cyclopentenes

Abstract: A novel reactivity of organoboronic acids with bicyclic hydrazines leading to the stereoselective formation of trans-vicinal disubstituted cyclopentenes in good to excellent yield is discussed. The reaction of cyclopentadiene and fulvene derived azabicyclic alkenes with organoboronic acids afforded the trans-3,4-disubstituted cyclopentenes and alkylidene cyclopentenes in good to excellent yields. The products, having a broad range of substituents, are important intermediates in the synthesis of a number of pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The carbonsilicon bond of allyltrimethylsilane, although less polarized, has sufficient nucleophilicity to react with palladium complexes. 27 As expected, the reaction of bicyclic hydrazine 1a with allyltrimethylsilane (38) in the presence of a palladium/Lewis acid catalyst afforded allyl-substituted hydrazinocyclopentene 27a as the product, but in low yield (Scheme 17). The reaction was found to be general for bi-and tricyclic olefins.…”
Section: Reactions With Organosilanesmentioning
confidence: 71%
See 1 more Smart Citation
“…The carbonsilicon bond of allyltrimethylsilane, although less polarized, has sufficient nucleophilicity to react with palladium complexes. 27 As expected, the reaction of bicyclic hydrazine 1a with allyltrimethylsilane (38) in the presence of a palladium/Lewis acid catalyst afforded allyl-substituted hydrazinocyclopentene 27a as the product, but in low yield (Scheme 17). The reaction was found to be general for bi-and tricyclic olefins.…”
Section: Reactions With Organosilanesmentioning
confidence: 71%
“…Other organometallic reagents, such as organosilanes, organoboronic acids, and organoindium reagents, were also found to be effective in the palladium-catalyzed desymmetrization of pentafulvene-derived bicyclic hydrazines (Scheme 24). 25,38 Thus, we had developed a general and efficient methodology for the synthesis of substituted alkylidenecyclopentenes.…”
Section: Reactivity Of Pentafulvene-derived Bicyclic Hydrazinesmentioning
confidence: 99%
“…A great deal of work has been carried out by Radhakrishnan and co‐workers using Pd(OAc) 2 with the assistance of iodine [68] . The reaction of cyclopentadienes and fulvene derived bicyclic hydrazines with boronic acids afforded trans ‐vicinal disubstituted cyclopentenes in good to excellent yield albeit in a racemic fashion [69] . The use of palladium catalysts in the asymmetric ring opening of bicyclic hydrazines with arylboronic acids is limited to the use of very particular chiral NHC−Pd(OAc) 2 as reported by Shi and co‐workers [70] .…”
Section: Boronic Acids and Derivativesmentioning
confidence: 99%
“…10 Recently, Shi et al reported the synthesis of trans-substituted alkylidenecyclopentenes via the ring-opening rearrangement of methylenecyclopropyl-substituted alkenyl derivatives. 11 In the context of our general interest in pentafulvenederived bicyclic hydrazines, we have unraveled a facile method for the construction of alkylidenecyclopentenes through palladium/Lewis acid catalyzed ring opening of fulvene-derived azabicyclic olefins with hard nucleophiles like organostannanes, 12 silanes, boronic acids, 13 and allylindium reagents. 14 All these reactions furnished trans-4,5-disubstituted 1-alkylidenecyclopent-2-ene derivatives.…”
mentioning
confidence: 99%